Drought characterization using drought indices in two areas of the Mediterranean basin: Meknès, Morocco, and Córdoba, Spain - Aghrab A.; Bouabid R.; Chafai Elalaoui A. (Drought management: scientific and technological innovations, 2008)
In this paper, drought events were characterized using drought indices in two zones: Meknès, Morocco, and Córdoba, Spain. The Standard deviation method was used to determine drought thresholds on an annual basis, while the deciles method was used to identify the seasonal drought thresholds at the season level (monthly and 10-days periods). The standard deviation method was enabled to determine drought severity classes for the percent-to-normal index, the rainfall deficit index, the climatic deficit index and the standardized precipitation index. A yearly classification was also determined based on drought occurrence in relation to crop growth stage of the main rain-fed crops in Morocco and Spain namely cereal and olive.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)